Nutraceutical Effect of Ganoderma lucidum Fungus on Neonatal Broilers Diet - Molina, D.S.; Gutierrez, J.B.; Machado, O.D.; Mas, D.; Martinez , Y. (International Journal of Poultry Science, 2019)
Background and Objective: The daily use of sub-therapeutic antibiotics in birds causes microbial resistance and cross resistance to other microorganisms, which directly affects poultry production. The objective of this study was to evaluate the nutraceutical effect of the Ganoderma lucidum fungus on growth performance, relative weight of the visceral organs and the count of cecal lactic acid bacteria of neonatal broilers. Materials and Methods: Three experimental treatments were applied: a basal diet (T0); T0+0.25% of Ganoderma lucidum and T0+0.50% of Ganoderma lucidum. Results: Supplementation with Ganoderma lucidum did not change the initial body weight, viability, feed intake and feed conversion, however, the addition of 0.25% promoted a higher body weight compared to the control. Also, this natural product significantly reduced (p0.05) for the other organs. In addition, the dietary use of this fungus up to 0.5% did not modify irregular white bacilli, green bacilli with white halo and white coccus. Conclusion: Dietary supplementation with 0.25% improved the body weight of the broilers, without modifying the feed intake and feed conversion, as well as modified some digestive and immune organs, although without changes for the count of the cecal lactic acid bacteria.